2015
DOI: 10.1242/dev.125807
|View full text |Cite
|
Sign up to set email alerts
|

Hippo signaling is required for Notch-dependent smooth muscle differentiation of neural crest

Abstract: Notch signaling has well defined roles in the assembly of arterial walls and in the development of the endothelium and smooth muscle of the vasculature. Hippo signaling regulates cellular growth in many tissues, and contributes to regulation of organ size, in addition to other functions. Here, we show that the Notch and Hippo pathways converge to regulate smooth muscle differentiation of neural crest, which is critical for normal development of the aortic arch arteries and cranial vasculature during embryonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 44 publications
5
81
0
Order By: Relevance
“…Notch ligand binding induces sequential proteolytic cleavage of Notch receptors to generate Notch intracellular domain (NICD) (45), which enters the nucleus to participate in the transcriptional regulation of target genes (46)(47)(48). As with previous studies (49,50), the expression of jagged 1 (Jag1), which encodes the Notch ligand JAG1, and Notch genes were upregulated in the DKO liver ( Figure 1A and Supplemental Figure 1, A and B; supplemental material available online with this article; doi:10.1172/JCI88486DS1). We then examined Notch signaling activities directly and found that Notch reporter activity, NICD Data are expressed as the mean ± SEM.…”
Section: Mst2mentioning
confidence: 61%
See 1 more Smart Citation
“…Notch ligand binding induces sequential proteolytic cleavage of Notch receptors to generate Notch intracellular domain (NICD) (45), which enters the nucleus to participate in the transcriptional regulation of target genes (46)(47)(48). As with previous studies (49,50), the expression of jagged 1 (Jag1), which encodes the Notch ligand JAG1, and Notch genes were upregulated in the DKO liver ( Figure 1A and Supplemental Figure 1, A and B; supplemental material available online with this article; doi:10.1172/JCI88486DS1). We then examined Notch signaling activities directly and found that Notch reporter activity, NICD Data are expressed as the mean ± SEM.…”
Section: Mst2mentioning
confidence: 61%
“…Similarly, Jag1 induction by YAP/TAZ and NICD interaction could also be tissue context dependent. While 2 TEAD response elements in the JAG1 promoter and the YAP/TEAD complex were found to be essential for JAG1 induction in HCC cells (49), YAP has also been found to require NICD to induce Jag1 expression in an RBP-Jκ-dependent, but TEAD-independent, fashion in smooth muscle cells (50).…”
Section: Discussionmentioning
confidence: 97%
“…when the system is above the excitability threshold as when lowering Yap signaling for instance), Notch signaling would only be needed to synchronize oscillators. These effects might result in part from Yap interacting with Notch signaling as demonstrated in other systems (Manderfield et al, 2015; Totaro et al, 2017). Since the cyclic activity induced by LatA treatment was observed independently of γ-secretase activity, it raises the question of the pacemaker controlling Lfng oscillations, as this gene is considered a direct Notch target (Morales et al, 2002).…”
Section: Discussionmentioning
confidence: 92%
“…4). A recent study indicated that Yap and Taz deficiency gives rise to smooth muscle differentiation defects partially derived from the CNC (Manderfield et al, 2015). Given the similar vessel defects in Wnt1…”
Section: S)mentioning
confidence: 99%